PENGGUNAAN APLIKASI KAHOOT DAN QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PADA MATA KULIAH DASAR-DASAR AKUNTANSI - Selviani, Ayudho; Ayuni, Rossa (Universitas Muhammadiyah Metro, 2025)
The aim of this research is to determine the use of the Khoots and Quiziz applications as interactive learning media in basic accounting courses. The type of research used is qualitative research with observation, interview and documentation methods. The research subjects included first semester economic education students. The research results show that the use of the Kahoot and Quiziz applications as interactive learning media in basic accounting courses is very good for use in the teaching and learning process in the classroom and outside the classroom.